Hydrolysis of the amorphous silica surface. II. Calculation of activation barriers and mechanisms - Walsh, T; Wilson, M; Sutton, A (American Inst of Physics, 2000)
The dry, amorphous, hydrophilic SiO2 surface is analyzed using cluster models. The reactivity of generic defect sites on the surface is analyzed with respect to water. The local network rearrangement that accompanies hydrolysis at these sites are studied.